Pengaruh Persepsi Kegunaan Dan Persepsi Resiko Terhadap Niat Pembelian Ulang Food Delivery App Pada Generasi Milenial Dengan Kepercayaan Sebagai Variabel Mediasi - Eryan Naufal Fakhri Muhammad Daffa; Aflit Nuryulia Praswati (JURNAL LENTERA BISNIS, 2023)
This study aims to determine the effect of perceived usefulness and perceived risk on repurchase intentions mediated by trust. This research uses quantitative methods. The population in this study is the millennial generation who use the Food Delivery App. The sampling technique in this study is non-probability sampling. The sampling technique used is purposive sampling. To conduct this research, researchers took as many as 160 respondents. The data collection method used in this study was by distributing questionnaires via the Google form. The questionnaire was created using a Likert scale format and processed using the Partial Least Square (PLS) analysis tool. This analysis process is carried out using the Smart PLS 3.2 application. The results showed that warning of use had a positive and significant effect on repurchase intention, perceived risk had a negative and significant effect on repurchase intention, perceived use had a positive and significant effect on trust, risk warning had a negative and significant effect on trust, trust had a positive and significant effect on repurchase intention, trust mediates the effect of perceived usefulness on repurchase intention, and trust is unable to mediate the effect of perceived risk on repurchase intention.Keywords: Perceived usefulness, Repurchase intention, Perceived risk, Trust